FACTORS OF THE ACUTE PHASE OF INFLAMMATION AS MODULATORS OF THE INTERACTION OF MAST CELLS AND FIBROBLASTS - S. A. Trulioff; I. V. Kudryavtsev; P. G. Nazarov (Acta Biomedica Scientifica, 2012)
We investigated the influence of factors of the acute phase of inflammation (purified anaphylatoxins C3a and C5a, pentraxin C-reactive protein (CRP), and aggregated. IgG (aIgG) — as an analogue of circulating immune complexes) on the adhesive interaction of human mast cells (MC) with human fibroblasts (FB). HMC-1 MC line and primary human foreskin FB were used. MC or FB were treated with each of the studied inflammatory proteins within 24 h and then the changes in their adhesive properties were examined. Cell adhesion was assessed by flow cytometry. The results showed that all studied proteins increased MC adhesiveness, whereas FB adhesiveness was increased only by anaphylatoxins. Stimulation of the adhesive properties of the MC was associated with increased expression of CD11b and ICAM-1 molecules.